'Authentic' folds: environmental audiences, activists and subjectification in hypocrisy micropolitics. Issue 6 (2nd November 2017) - Piotrowski, Marcelina
Abstract: This paper examines how the trope of authenticity is communicated and enacted in environmental movements. The paper employs Deleuze's concept of le pli, or the fold, and Deleuze and Guattari's concept of faciality to argue that political subjects in the environmental movement emerge through folding the preoccupation with authenticity that they observe in news media, oil pipeline advertising and environmental activists' campaigns, as a relationship they can develop to themselves. Taking a de-centred audience studies approach, this paper shows how authenticity is a state that can be acquired, sustained and lost through authenticity enactments and image relationships that work in relation to hypocrisy micropolitics . The paper argues that the preoccupation with authenticity events as a technology of subjectification becomes an object of concern for political subjects in social and environmental movements, and authenticy becomes an affective texture that is spatially and temporally produced.